Cultural Expertise in Italian Criminal Justice: From Criminal Anthropology to Anthropological Expert Witnessing - Anna Ziliotto (Laws, 2019)
This article traces the rise and fall of psychiatric evaluation in criminal trials from the School of Criminal Anthropology of the late nineteenth century to the current Italian justice system. Influenced by positivism and by specific theories on human evolution, Cesare Lombroso considered criminal action as the result of organic causes excluding any kind of legal autonomy and responsibility of the accused. The Positive School of Penal Law he founded with Enrico Ferri and Raffaele Garofalo profoundly inspired the Rocco Code, on which the current Italian Penal Code is still based, albeit with revisions and repeals. Drafted in 1930 during the fascist government (1922−1943), the latter has also suffered from racial ideology. In order to assess potential mental illnesses that would exclude the responsibility of the accused, to determine their level of dangerousness and to establish the corresponding security measures introduced by the Rocco Code, Italian criminal justice consolidated the link between penal law and psychiatric instruments. Such faith in psychiatric evaluation, however, has been particularly questioned by the increasing frequency of judicial processes involving members of different cultural communities in Italy since the 1970s. Thus, the predominantly pathological aspects evaluated by forensic psychiatrists have often proved to be conceptually and methodologically inadequate to take fully into account the differences between cultures, as well as the different social and cultural conditions affecting the defendant’s behaviour. This paper argues that cultural anthropology is particularly suited as an instrument capable of disclosing the cultural implications of the legal process and encourages the use of cultural expertise as an important tool for the inclusiveness and understanding of diversity.